Antibacterial effects of White Siris (Albizia procera) leaf and bark extracts on aquatic pathogenic bacteria (Aeromonas hydrophila ans Staphylcoccus aureus). - Balogo, Philip (UPHSI, 2011)
This study is aimed to determine if payhod leaf or bark extracts have antibacterial effects on Aeromonas hydrophila and Staphylococcus aureus. Using Kirby-Bauer Disc-susceptibility test, the aqueous extracts of both parts, prepared in 4 concentrations (25, 50, 75, and 100%), were tested on both pathogens. The study also included amoxicillin for positive control and water as negative control. The zones of inhibition, in millimetres, were computed by doubling the measurement from the nearest colony to the center of the disc impregnated with the extract. ANOVA and DMRT were used to determine if there are significant differences among the concentrations. The results showed that the leaf extract have antibacterial effects on both pathogens, while the bark extract showed no activity. Among the concentrations of the leaf extract, the 100% leaf extract gave the largest zones of inhibition. Payhod leaf extract is an effective antibacterial agent.